Information presentation: enhancing consumer purchase intention through nutritional supplement advertisement design - Sun, Shaobo; Cao, Jun; Wei, Yunyun; Yang, Dajun; Guo, Ke (Frontiers in Nutrition, 2025)
In recent years, how nutritional supplement advertisement design effectively influences purchase intention has emerged as a critical research focus. Traditional studies predominantly emphasize product attributes but overlook how the presentation of product features impacts consumer psychology. Through three experiments, this research investigates the differential effects of internal structural presentation (deconstructed) vs. holistic presentation in nutritional supplement advertisements and elucidates their underlying mechanisms. Experiment 1 (N = 305) revealed that the structural presentation group significantly enhanced consumers’ quality perception compared to the holistic presentation group. Experiment 2 (N = 229), utilizing a chain mediation model, demonstrated that uncertainty avoidance and panic buying mediate the impact of structural presentation on purchase intention. Experiment 3 (N = 304) further identified an interaction between technological anxiety and advertisement visual design: structural presentation exerted stronger effects when high-quality visual design alleviated technological anxiety. This study advances advertisement design theory by highlighting how structural presentation shapes decision-making through psychological mechanisms, offering novel insights for consumer behavior research. The findings provide actionable recommendations for nutritional supplement companies to optimize advertisement design by integrating technical details with visual appeal and strategically addressing consumer anxiety to enhance marketing effectiveness.